Merdeka Curriculum: How the Profile of Planning for Mathematics Learning by Teachers? - Krisma, Dita Aldila; Muqtada, Moh. Rikza; Khasanah, Fitria Uswatun (Department of Mathematics Education Program IPI Garut, 2024)
Pebedaan fasilitas yang diterima satuan pendidikan terkait implementasi Kurikulum Merdeka berpengaruh terhadap perbedaan tingkat pemahaman guru antar sekolah. Tujuan penelitian ini adalah mendeskripsikan perencanaan pembelajaran matematika dalam Kurikulum Merdeka di tingkat SMP di Kota Magelang. Urgensi penelitian ini adalah perlunya gambaran implementasi pembelajaran matematika dalam Kurikulum Merdeka di tingkat satuan pendidikan dari segi perencanaan untuk bahan evaluasi dan inspirasi pembelajaran matematika dalam implementasi Kurikulum Merdeka. Penelitian ini merupakan penelitian kualitatif dengan metode deskriptif. Penelitian dilaksanakan di tujuh SMP negeri di Kota Magelang. Teknik utama pengambilan data melalui wawancara dengan satu guru matematika pengampu kelas 7 di tiap sekolah. Teknik analisis data yang digunakan meliputi pencatatan data hasil wawancara dan dokumentasi, pengkodean data, olah data, analisis data, dan interpretasi data. Hasil penelitian mendeskripsikan perencanaan pembelajaran matematika dalam Kurikulum Merdeka tingkat SMP di Kota Magelang meliputi CP, TP, ATP, modul ajar, dan, asesmen. Rata-rata, guru melakukan modifikasi dalam penyusunan perangkat ajar disesuaikan dengan kebutuhan peserta didik sekolah masing-masing. The differences in facilities received by educational units related to the implementation of the Independent Curriculum influence differences in the level of teacher understanding between schools. The purpose of this study is to describe mathematics learning planning in the Merdeka Curriculum at the junior high school level in Magelang City. The urgency of this research is the need for a description or description of the implementation of mathematics learning in the Merdeka Curriculum at the education unit level in terms of planning so that it can be used as an evaluation and inspiration for mathematics learning in implementing the Merdeka Curriculum. This research is a qualitative research with descriptive method. This research was conducted in seven public junior high schools in Magelang City with the main technique of data collection through interviews with one 7th grade math teacher in each school. The data analysis technique used in this research includes recording data from interviews and documentation, then coding data, processing data, analyzing data, interpreting data. The results of this study describe mathematics learning planning in the Merdeka Curriculum at the junior high school level in Magelang City including CP, TP, ATP, teaching modules, and, assessment. On average, teachers modify existing documents and adapt them to the needs of students in their respective schools.